2009
DOI: 10.1016/j.bpj.2009.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Dissociation Constants in Living Zebrafish Embryos with Single Wavelength Fluorescence Cross-Correlation Spectroscopy

Abstract: The quantification of biological interactions is very important in life sciences. Here we report for the first time, to our knowledge, the determination of a biomolecular dissociation constant (K(D)) in living zebrafish embryos at physiological protein expression levels. For that purpose, we extend the application of single wavelength fluorescence cross-correlation spectroscopy into small organisms and measure the interaction of Cdc42, a small Rho-GTPase, and IQGAP1, an actin-binding scaffolding protein. Cdc42… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
77
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 41 publications
2
77
0
Order By: Relevance
“…Fluorescence correlation spectroscopy (FCS) is widely used for measuring protein dynamics in live cells [1][2][3][4] and organisms [5][6][7][8]. FCS measures the dynamic properties of particles in a small laser focus by analyzing the emitted fluorescence fluctuations with a correlation analysis [9].…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescence correlation spectroscopy (FCS) is widely used for measuring protein dynamics in live cells [1][2][3][4] and organisms [5][6][7][8]. FCS measures the dynamic properties of particles in a small laser focus by analyzing the emitted fluorescence fluctuations with a correlation analysis [9].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a few reports have measured dissociation constants in living cells (here referred to as the "in vivo K d ") (Fig. 1B) by means of intermolecular fluorescence resonance energy transfer (FRET), single-molecule fluorescence imaging, and fluorescence cross-correlation spectroscopy (FCCS) (9)(10)(11)(12). All of these techniques employ twocolor fluorescence imaging.…”
mentioning
confidence: 99%
“…Conversely, the cytoplasm of Escherichia coli was shown to destabilize the IgG binding domain of protein L (8). With respect to protein binding, it was shown that the affinity of Cdc42 to various proteins increases in eukaryotic cells (9), with a 10-fold difference between cell types (10). The dynamics of α 2A -adrenergic receptors binding to G proteins was monitored by Förster resonance energy transfer (FRET)-based assay, but no direct comparison to in vitro rate constants was made (11).…”
mentioning
confidence: 99%